Acute flaccid myelitis and Guillain–Barré syndrome in children: A comparative study with evaluation of diagnostic criteria. (24th November 2021) - Helfferich, Jelte; Roodbol, Joyce; de Wit, Marie‐Claire; Brouwer, Oebele F.; Jacobs, Bart C.; ,
Abstract: Background and purpose: Differentiation between acute flaccid myelitis (AFM) and Guillain–Barré syndrome (GBS) can be difficult, particularly in children. Our objective was to improve the diagnostic accuracy by giving recommendations based on a comparison of clinical features and diagnostic criteria in children with AFM or GBS. Methods: A cohort of 26 children with AFM associated with enterovirus D68 was compared to a cohort of 156 children with GBS. The specificity of the Brighton criteria, used for GBS diagnosis, was evaluated in the AFM cohort and the specificity of the Centers for Disease Control and Prevention (CDC) AFM diagnostic criteria in the GBS cohort. Results: Children with AFM compared to those with GBS had a shorter interval between onset of weakness and nadir (3 vs. 8 days, p < 0.001), more often had asymmetric limb weakness (58% vs. 0%, p < 0.001), and less frequently had sensory deficits (0% vs. 40%, p < 0.001). In AFM, cerebrospinal fluid leukocyte counts were higher, whereas protein concentrations were lower. Spinal cord lesions on magnetic resonance imaging were only found in AFM patients. No GBS case fulfilled CDC criteria for definite AFM. Of the AFM cases, 8% fulfilled the Brighton criteria for GBS, when omitting the criterion of excluding an alternate diagnosis. Conclusions: Despite the overlap in clinical presentation, we found distinctive early clinical and diagnostic characteristics for differentiating AFM from GBS in children. Diagnostic criteria for AFM and GBS usually perform well, but some AFM cases may fulfill clinical diagnostic criteria for GBS. This underlines the need to perform diagnostic tests early to exclude AFM in children suspected of atypical GBS. Abstract : A child with acute onset flaccid weakness may pose a diagnostic challenge for clinicians, with both acute flaccid myelitis (AFM) and Guillain–Barré syndrome (GBS) included in the differential diagnosis. We provide distinguishing features and recommendations, which may help clinicians in making the right diagnosis. In cases of atypical GBS, the diagnosis of AFM needs to be excluded early in the disease course, as AFM may fulfill the current clinical, cerebrospinal fluid, and nerve conduction studies diagnostic criteria for GBS.